GAMBARAN KEMAMPUAN, LINGKUNGAN KERJA SOSIAL DAN KINERJA KARYAWAN - Dewi, Desita Anggra; Senen, Syamsul Hadi; Masharyono, Masharyono (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - The purpose of this study is to see the description of ability, social work environment, and performance.The design / methodology / approach - The design of this study was cross sectional. This research uses descriptive approach with explanatory survey method. The employee analysis unit is 103 people. Data collection using questionnaire. The analysis technique used is descriptive technique by using frequency distributionFindings – Based on the results of research using descriptive analysis, the results obtained that ability in the very good category, social work environment in the very conducive category, and performance in the high category.Originality - This study provides a basis for understanding the issues of the ability and social work environment on performance. The difference of this research with previous research is on the object in PT. Indorama Synthetics Tbk. Polyester Division In Purwakarta, ability variable, social work environment and performance, and references used by researchers with previous researchers.